2017
DOI: 10.1016/j.anbehav.2017.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Leaf extracts from an exotic tree affect responses to chemical cues in the palmate newt, Lissotriton helveticus

Abstract: Chemical communication in aquatic species can affect many key life history traits, such as prey and predator detection and mate searching. However, changes in the environment can disrupt the effectiveness of signals and the ability of individuals to detect these signals. Many studies have examined the effect of secondary compounds from exotic plants on the ecology and physiology of a range of taxa, but whether the replacement of natural forests with exotic trees influences the behavioural responses of animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…First, urban habitats could disrupt intraspecific communication of species that use coloration as a signal when competing for mates. Previous studies often show that signal transmission and reception is less efficient when animals are taken out of the environment in which they evolved [23,24]. If urban habitats disrupt visual signalling, we might expect links between the signal and male quality to be weakened leading females to mate with poor quality mates which could impact on the viability of future generations.…”
Section: Discussionmentioning
confidence: 99%
“…First, urban habitats could disrupt intraspecific communication of species that use coloration as a signal when competing for mates. Previous studies often show that signal transmission and reception is less efficient when animals are taken out of the environment in which they evolved [23,24]. If urban habitats disrupt visual signalling, we might expect links between the signal and male quality to be weakened leading females to mate with poor quality mates which could impact on the viability of future generations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the indications of physiological stress were not severe, as eucalypt leaf litter had scarcely any effect on the immune status or oxidative stress of larvae. Therefore, we consider that eucalypt leachates were more likely interfering with predator recognition and not necessarily impairing their ability to respond, as was the case in other cases of non-native plant leachates ( Hickman and Watling, 2014 ; Iglesias-Carrasco et al , 2017b ), or more generally with other alterations of the ponds’ chemosphere ( Polo-Cavia et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, despite the large extent of eucalypt reforestations worldwide, the effects of eucalypt plantations on aquatic vertebrates (and particularly on amphibians) have received very little attention (but see Iglesias-Carrasco et al , 2016 and Iglesias-Carrasco et al , 2017a ). Although it has recently been shown that eucalypt leaf litter can impair mate and predator recognition in adult newts ( Iglesias-Carrasco et al , 2017b ), the extent to which it also affects growth, development or physiology of amphibian larvae is virtually unknown. To this end, we designed an experiment in which larvae of the European common frog ( Rana temporaria ) were exposed to either eucalypt or native oak leaf litter under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fork et al (2015) found lower arthropod richness and lower abundance of some arthropod classes in Eucalyptus relative to oak woodland habitat-although an earlier study did not find differences in leaf litter arthropod richness in Eucalyptus vs. Quercus woodlands; Sax, 2002. In addition, Eucalyptus leaf extract has been found to compromise chemical communication in salamanders, and this could contribute to stress in Batrachoseps residing in invasive vegetation dominated habitat (Iglesias-Carrasco et al, 2017). Ultimately, a more comprehensive comparison of abiotic and biotic characteristics in relevant microhabitats is needed to fully understand the effects of invasive vegetation on terrestrial salamanders.…”
Section: Potential Effects Of Eucalyptus Invasion On Batrachoseps Attmentioning
confidence: 94%